2022
DOI: 10.15252/msb.202110704
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis/gluconeogenesis specialization in microbes is driven by biochemical constraints of flux sensing

Abstract: Central carbon metabolism is highly conserved across microbial species, but can catalyze very different pathways depending on the organism and their ecological niche. Here, we study the dynamic reorganization of central metabolism after switches between the two major opposing pathway configurations of central carbon metabolism, glycolysis, and gluconeogenesis in Escherichia coli , Pseudomonas aeruginosa , and Pseudomonas putida . We combined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…The first interaction is the feedforward activation of pyruvate kinase (PYK) by fructose-1,6-bisphosphate (FBP), which plays an important role for glycolysis flux regulation in E. coli 61 . The other two interactions represent negative feedbacks from phosphoenolpyruvate (PEP) to the interconversion of hexose-phosphate and FBP, by respectively inhibiting phosphofructokinase (PFK) and activating fructose-1,6-bisphosphatase (FBPase), which together regulate the PFK-FBPase cycle 62 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The first interaction is the feedforward activation of pyruvate kinase (PYK) by fructose-1,6-bisphosphate (FBP), which plays an important role for glycolysis flux regulation in E. coli 61 . The other two interactions represent negative feedbacks from phosphoenolpyruvate (PEP) to the interconversion of hexose-phosphate and FBP, by respectively inhibiting phosphofructokinase (PFK) and activating fructose-1,6-bisphosphatase (FBPase), which together regulate the PFK-FBPase cycle 62 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This post-transcriptional regulation has evident physicochemical advantages, which allow for an extremely rapid and sensitive response to substrate availability. In P. putida, this mechanism confers a preference for gluconeogenic substrates 33,56,57 , although studies have previously demonstrated that in nutritionally complex environments, glycolytic and gluconeogenic co-utilisation can coexist 45,[58][59][60] . In this current work, we showed that lactic acid is preferentially consumed, and C5 sugars and aromatics were least favoured.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas putida is a soil dwelling bacterium that displays high solvent tolerance and is considered to be a robust host for bioproduction and bioremediation applications 31,32 . It possesses remarkably flexible non-archetypal metabolism that can accept divergent carbon substrates with no overflow metabolism and rapid shift/adaptation to nutrient availability without a long lag-phase 33 .…”
mentioning
confidence: 99%
“…Since the Pelz et al (1999) publication, there have been a number of studies that indicate that the Pareto principle may apply widely to stable microbial communities, often in the context of metabolic trade‐offs (e.g., De Vrieze & Verstraete, 2016; Fuentes et al, 2021; Marzorati et al, 2008; Mertens et al, 2005; Schink et al, 2022), but also in terms of the relationship between cell morphology and function (Schuech et al, 2019; Sheftel et al, 2013; Shoval et al, 2012), the composition of human microbiome communities (Heinken & Thiele, 2015a, 2015b), and the biotechnological use of microbes for the production of chemicals (Amaradio et al, 2022).…”
Section: Other Examples Of Pareto‐conform Microbial Communitiesmentioning
confidence: 99%